Risk Factors of Dementia in Elderly of Bandung City, Indonesia: A Community-Dwelling Study - Sarah Fitri Janaris; Sharon Gondodiputro; Nita Arisanti (Faculty of Medicine Universitas Padjadjaran, 2020)
Background: Multiple organ degenerative processes are parts of a normal biological process in aging. One of the geriatric syndromes is cognitive disorders that range from a mild cognitive impairment to dementia. The aim of this study was to analyze factors contributing to the occurrence of dementia in the elderly.Methods: A cross-sectional analytical study was conducted using secondary data on 306 elderly people who visited the Integrated Health Post (Pos Pembinaan Terpadu, Posbindu) from June to August 2016 in Bandung City, Indonesia. Nine variables were included in this study: age, gender, education level, marital status, occupation, living arrangements, social participation, comorbidity, and dementia. The dementia status was measured by the Mini-Mental State Examination and Mini Cog Assessment instruments. Data were then analyzed statistically using Chi-Square, Fisher Exact, and Kolmogorov-Smirnov tests, as well as using the multivariate logistic regression.Results: Around 35.3% (95%CI=30%–40.6%) of respondents had dementia. There were relationships between dementia and age (p=0.035), level of education (p=0.000), and social participation (p=0.001). Social participation was the most dominant risk factor of dementia (OR=2.703;95%CI=1.491-4.902).Conclusions: Age, education level, and social participation are risk factors that contribute to dementia. The elderly who has less than two times per week of social participation has a 2.7 times higher risk for having dementia compared to the elderly who has more than two times per week of social participation.